Deconstructing doing well; what can we learn from care experienced young people in England, Denmark and Norway?. (November 2020) - Bakketeig, Elisiv; Boddy, Janet; Gundersen, Tonje; Østergaard, Jeanette; Hanrahan, Fidelma
Highlights: This paper analyses narratives of 'doing well' for 15 care-experienced young adults Participants were part of a larger study in Denmark, England and Norway. All were in education, employment or training. Analysis shows the value of a broad conceptualization of outcomes. Professionals need to recognize the complexities of doing well over time. Abstract: This paper addresses the conceptualization of 'outcomes' for care experienced people through an in-depth longitudinal study of 75 young adults in Denmark, England and Norway. 'Outcome' studies have played a crucial role in raising awareness of the risk of disadvantage that care experienced people face, across a variety of domains including education and employment. These studies may have an unintended consequence, however, if care experienced people are predominantly viewed, and studied, through a problem-focused lens. The danger is that policy and research neglects other – perhaps less readily measurable – aspects of experience, including subjective understandings – what matters to care experienced people themselves. Our analyses are based on an in-depth qualitative longitudinal study, which explored meanings of 'doing well' over time among care experienced people (aged 16–32), all of whom were 'successful' in relation to traditional indicators of participation in education and/or employment (including voluntary work). Across countries, their accounts revealed the importance of attending to subjective and dynamic understandings of 'doing well', and the significance of ordinary, mundane and 'do-able' lives. Participants' narratives highlight aspects of doing well that raise challenging questions about how traditional outcome indicators – and corresponding policy priorities – might better capture what young people themselves see as important. A narrow interpretation of outcomes may lead to mis recognition of what it means to do well, and so to a stigmatizing 'way of seeing' care experienced lives. A broader conceptualization of outcomes is necessary to recognize – and so to develop policy and services to support – the complex, dynamic relationality of doing well.